2011
DOI: 10.1262/jrd.10-121n
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular Expression of mRNAs of Both Interferon γ and Tumor Necrosis Factor α is Significantly Increased in Experimental Autoimmune Orchitis in Mice

Abstract: Abstract. Experimental autoimmune orchitis (EAO) is one of the models of immunological male infertility. Murine EAO is CD4+T cell-dependent and classically induced by immunization with a testicular homogenate and adjuvants. We previously established that immunization with viable syngeneic testicular germ cells (TGC) can also induce murine EAO with no use of any adjuvant. Analyses of this EAO model have already revealed that cultured spleen cells of immunized mice secreted interferon (IFN)-γ and that treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Furthermore, TNF, a strong pro-inflammatory cytokine, was increased in our model of EAEO, similar to other mouse models of testicular inflammation induced by viable germ cells 64 or adoptive transfer by using testis and sperm-antigen specific T cell clones 65 . An increase was detected also in testicular mRNA levels for MCP-1, a potent chemokine, involved in recruiting the immune cells to the site of inflammation.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, TNF, a strong pro-inflammatory cytokine, was increased in our model of EAEO, similar to other mouse models of testicular inflammation induced by viable germ cells 64 or adoptive transfer by using testis and sperm-antigen specific T cell clones 65 . An increase was detected also in testicular mRNA levels for MCP-1, a potent chemokine, involved in recruiting the immune cells to the site of inflammation.…”
Section: Discussionsupporting
confidence: 82%
“…It was demonstrated that antisperm antibodies can be a common reason of male infertility also in association with the cytokine presence and that infection/inflammation of the male genital tract, systemic infection or illness may deteriorate the testicular function [ 24 ]. Conversely, secondary autoimmune orchitis can be represented by testicular vasculitis associated with systemic autoimmune diseases such as polyarteritis nodosa, Behçet's disease, and rheumatoid arthritis [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such patients have increased levels of Th17 cells, their cytokines such as IL-17A, IL-21, and IL-22, and IL-23-producing CD11c + DCs and CD68 + macrophages [137]. Moreover, because IL-17 was expressed not only in normal testis but also in higher levels in azoospermic testis, IL-17 might be involved in the maintenance of testicular immune privilege and spermatogenesis [137, 138]. In addition, pro-inflammatory cytokines including IL-1 and IL-6 have direct effects on spermatogenic cell differentiation and testicular steroidogenensis within the normal testis [139].…”
Section: Th17 Cells In Testesmentioning
confidence: 99%